Employees’ Competency Mapping Among Spinning Mills in Rajapalayam – an Empirical Research - V, Aghalya; Raman R, Kasi; S, Kottathai; M, Indhuja (International Journal of Scientific Research and Management (IJSRM), 2021)
Competency mapping is a process through which one assesses and determines one’s strengths as an individual worker and in some cases, as part of an organization. It generally examines two areas: emotional intelligence or emotional quotient (EQ), and strengths of the individual in areas like team structure, leadership, and decision-making. The significant of differentiating competencies into different types such as conceptual, technical, contextual, interpersonal, etc. has gained momentum. Consequently, understanding the abilities, intentions, concealed possibilities, qualities of the people working in the association is critical. Every job has its own profile and specification. The research involved a survey in which total of two hundred and fifty employees drawn from various spinning mills in Rajapalayam were used as subjects. It is examined with the help of statistical tool together with various demographical factors was also studied using simple Percentage analysis, Weighted Average and Chi – square test. Data was collected through questionnaire and analyzed through SPSS. The chi-square analysis shows that there is significant Relationship between age of the respondents and knowledge of the respondents and also shows that there is significant Relationship between experience of the respondents and job performance of the respondents.